The Influence of commercial banks’ products accessibility strategy on growth of MSEs in Kenya - Kathuku, Jane Karambu; Ngugi, Dr. Patrick Karanja; Muturi, Dr. Willy (European Journal of Business and Strategic Management, 2016)
Purpose: The main purpose of this study was to establish the influence of commercial banks' products accessibility strategy on growth of MSEs in Kenya Methodology: The study employed a descriptive survey design with a population of 2,519,457 MSEs in Kenya and the chief credit officers from the 44 commercial banks in Kenya. The bank chief credit officers and MSEs owners were targeted for information by this study because they were likely to be the decision makers. The chief credit officers who were sampled from the headquarters of the commercial banks were actively involved in making lending decisions. The researcher used purposive sampling to select respondents. The sample size which was purposively selected was comprised of 352 respondents. The study will use questionnaires to collect data from the field. Both quantitative and qualitative data gathered will be coded and analyzed using Statistical Package for Social Sciences (SPSS) computer software. Descriptive statistics was used to analyze the data in frequency distributions and percentages which were presented in tables and figures. Inferential statistics were used to analyze qualitative data. Results: The study found out that commercial banks' product accessibility have a positive and significant effect on MSEs growth. Unique contribution to practice and policy: Based on the findings of the study, recommended that commercial banks should ensure that their products are accessible since it leads to MSEs Growth.